Stabilization of a light bullet in a layered Kerr medium with sign-changing nonlinearity - Adhikari, S. K. (Amer Physical Soc, 2004)
Using the numerical solution of the nonlinear Schrodinger equation and a variational method, it is shown that (3+1)-dimensional spatiotemporal optical solitons, known as light bullets, can be stabilized in a layered Kerr medium with sign-changing nonlinearity along the propagation direction.